Use of Social Media in Marketing Library Resources and Services - Kirita, Fortunata Francis; Mwantimwa, Kelefa (University of Dar es Salaam Library Journal, 2022)
This study has investigated the use of social media in marketing library resources and services at MUHAS and SUA. A mixed research approach was used to process, collect and analyse data in the study. While some library staff and all users were conveniently selected, key informants were purposively selected. The data were mainly collected through survey methods. The qualitative data collected were subjected to content analysis while quantitative data were analysed using SPSS. The study ' s findings suggest that Facebook is the effectively used platform by both the studied libraries in the marketing of library services and resources due to its popularity and convenience. The other effectively used media is WhatsApp, although this was noted only at MUHAS. However, notwithstanding this, the media ' s usage to market library resources and services has been found generally ineffective. This has been attributed to different challenges such as lack of a written policy for social media usage, unreliable internet connectivity, low promotion, content obsoleteness, and inadequate computer facilities. The study recommends that social media policies should be formulated, investment in ICT infrastructure development should be made, and promotion of social media usage among information users should be done.